A systematic framework for predictive biomarkers in immune effector cell-associated neurotoxicity syndrome - Butt, Omar H.; Zhou, Alice Y.; Ances, Beau M.; DiPersio, John F.; Ghobadi, Armin (Frontiers in Neurology, 2023)
Chimeric antigen receptor (CAR)-T cell therapy has revolutionized the management of several life-threatening malignancies, often achieving durable sustained responses. The number of patients treated with this new class of cell-based therapy, along with the number of Food and Drug Association (FDA) approved indications, are growing significantly. Unfortunately Immune Effector Cell-Associated Neurotoxicity Syndrome (ICANS) can often occur after treatment with CAR-T cells, and severe ICANS can be associated with significant morbidity and mortality. Current standard treatments are mainly steroids and supportive care, highlighting the need for early identification. In the last several years, a range of predictive biomarkers have been proposed to distinguish patients at increased risk for developing ICANS. In this review, we discuss a systematic framework to organize potential predictive biomarkers that builds on our current understanding of ICANS.